Developing Early Childhood Creativity Through Painting Activities Using Cotton Buds at PAUD MTA Pontianak - Musrimah, Musrimah; Sudarti, Sudarti; Yuniarti, Yuniarti (Kepompong Children Centre Journal, 2025)
This study aims to describe the use of cotton buds as a painting medium to enhance early childhood creativity at PAUD MTA Pontianak. The research used a descriptive qualitative method, with data collected through observation, interviews, and documentation. The subjects were group B children aged 5–6 years and their classroom teacher. The results showed that using cotton buds with pointillism techniques provided children with broad opportunities to explore, express imagination, and develop fine motor skills. Teachers played a crucial role in planning, demonstrating, and actively guiding the process. Despite challenges such as limited motor coordination, teachers’ artistic skills, and media quality, solutions were addressed through individual approaches, basic training, and method innovation. The painting activity proved effective in fostering creativity, independence, and self-expression among early childhood learners in an enjoyable and meaningful learning atmosphere.